Undi18 : Role of Social Media in Shaping the Political Literacy of Young Sarawakian Voters - Elvydina, Barnad; Ting, Su Hie; Kai, Zhang; Ernisa, Marzuki; Siti Haslina, Hussin (Asian Scholars Network (ASNet), 2025)
The study examined the role of social media in shaping the political literacy of youth in Sarawak. The specific aspects studied were online political engagement, sources of political news, preferred social media platforms for political information, and factors motivating online political engagement. Questionnaire data from 41 participants aged 18-21 living in Kuching Sarawak were analysed. The results showed high consumption of political news, particularly on TikTok, Facebook, and Instagram. Social media was the main source of political news for 95.1% of participants but television and online newspapers still have a role to play in disseminating political information to young voters. Family, peers, and teachers are hardly political socialisation agents for the youth of today. The participants found news updates as the most useful and interesting political posts on social media, but personal stories and numbers did not appeal to them. Their main reason for accessing political news was to gain new insights but political participation and activism were low on their priority. The findings indicated educational efforts are more effective when delivered through non-intrusive news content rather than overt promotional messages or calls to action.